2022
DOI: 10.3389/fimmu.2022.847624
|View full text |Cite
|
Sign up to set email alerts
|

A Necroptosis-Related Prognostic Model of Uveal Melanoma Was Constructed by Single-Cell Sequencing Analysis and Weighted Co-Expression Network Analysis Based on Public Databases

Abstract: BackgroundUveal melanoma(UVM) is the most common intraocular malignancy and has a poor prognosis. The clinical significance of necroptosis(NCPS) in UVM is unclear.MethodsWe first identified necroptosis genes in UVM by single-cell analysis of the GSE139829 dataset from the GEO database and weighted co-expression network analysis of TCGA data. COX regression and Lasso regression were used to construct the prognostic model. Then survival analysis, immune microenvironment analysis, and mutation analysis were carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 34 publications
(43 reference statements)
1
37
0
Order By: Relevance
“…Notably, the high-risk and low-risk groups showed significant differences in immunocyte infiltration. These differences in immunocyte infiltration between the high-risk and low-risk groups has been found to exist in a variety of tumors [ 21 24 ]. Our results showed that the high-risk group presented relatively high distribution levels of monocytes, activated dendritic cells, activated mast cells, and eosinophils but relatively low distribution levels of resting NK cells and resting mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the high-risk and low-risk groups showed significant differences in immunocyte infiltration. These differences in immunocyte infiltration between the high-risk and low-risk groups has been found to exist in a variety of tumors [ 21 24 ]. Our results showed that the high-risk group presented relatively high distribution levels of monocytes, activated dendritic cells, activated mast cells, and eosinophils but relatively low distribution levels of resting NK cells and resting mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that SLC25A13 might be a good diagnostic molecule for SKCM. To further determine the survival of SKCM patients, we drew a nomogram combining the risk value and clinical characteristics of the model [ 28 ]. As shown in Figure 4 , we found that the 1-, 3-, and 5-year mortality rates of patient “TCGA-EE-A2A2-06” were 0.102, 0.478 and 0.64, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Its specific mechanism, such as the discovery of immune checkpoints such as PD-1/PDL-1 and CTLA-4, has brought reference for the treatment of many solid tumors ( Xie et al, 2021d ). Immunotherapy has achieved promising outcomes in tumor types such as melanoma ( Carreno et al, 2015 ; Cao et al, 2021 ; Xie et al, 2022 ). However, immunotherapy has progressed relatively slowly in breast cancer ( Emens, 2018 ).…”
Section: Discussionmentioning
confidence: 99%